Peningkatan Hasil Belajar Tematik Terpadu Siswa Menggunakan Model Kooperatif Tipe Talking Stick di Sekolah Dasar - Rasjulita, Irma Maulida; Zuryanty, Zuryanty (Universitas Negeri Padang, 2023)
This study aims to describe the increase in learning outcomes of integrated thematic learning using the talking stick cooperative model in V grade elementary school. This research is included in classroom action research using quantitative and qualitative approaches. In practice, this research was conducted in 2 cycles. Each cycle has stages of planning, implementing, observing, and reflecting. The subjects of the study were all 20 students of class V at SDN 11 Batang Anai. In the first cycle, the lesson plan was observed with an average of 87.5% (B) and increased in the second cycle with a value of 95% (SB). The results of monitoring teacher activity in cycle I with an average of 80.5% (B) experienced an increase in cycle II, namely 94.44% (SB). Furthermore, student activity in cycle I with an average acquisition of 80.5% (B) and increased 94.44% (SB) in cycle II. While student learning outcomes in cycle I obtained an average value of 74, increasing in cycle II with an average value of 88. It can be concluded that the talking stick type cooperative model can improve student learning outcomes in integrated thematic learning in class V of elementary school.